Median and Digital Nerve In Situ Tension in the Hand. (January 2022) - Didesch, Jacob T.; Schimoler, Patrick J.; Miller, Mark Carl; Tang, Peter
Background: Digital nerves will experience tension under normal daily activities, and understanding the amount of tension experienced in these nerves relates directly to the necessary strength in nerve repairs. To begin quantification of tension, the tension borne by the median and digital nerves in cadaveric hands was quantified under conditions of finger hyperextension, nerve distraction, and finger flexion.Methods: Five cadaveric hands were mounted in a special fixture that allowed finger hyperextension and flexion and could apply known distractions while the tension borne by each digital nerve was measured. Sequential dissection exposed the digital nerves so that measurements of tension in the median, common, and proper digital nerves were conducted with finger hyperextension, nerve distraction, and finger flexion.Results: Metacarpophalangeal (MCP) hyperextension of 30° created mean nerve tensions up to 0.64 N, 5 mm of nerve distraction created mean nerve tensions up to 1.23 N, and 90° of MCP flexion relieved up to a mean of 1.18 N of nerve tension.Conclusions: In situ tension is present in the median and digital nerves with digital motion. Finger hyperextension and nerve distraction produce tension, whereas finger flexion reduces tension. Existing nerve repairs are strong enough to withstand in situ nerve tensions produced by reasonable digital motion if the original nerve length is present.